A public communication and social representation theory approach on islamic issues in Indonesia - Khakim, Abdul (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: The rise of Islamic issues in Indonesia, which are generally packaged in various policies or programs, is often not responded to positively by the public. In some cases, such as the issue of waqf, zakat and Hajj, it actually receives counterproductive responses. Methods: This paper aims to study this social phenomenon using a two-theoretical approach, namely public communication and social representation as conceptualized by Serge Moscovici. To sharpen this theoretical study, this paper dissects two dissertations related to the preaching of the Prophet Muhammad and public policy of internalizing religious values in the city of Bandung. Results: This research shows that the theory of public communication and social representation is relevant for studying Islamic studies which continues to develop and is marked by the emergence of various social phenomena. Conclusion: However, the results of this theoretical approach are not standard because Islamic issues are influenced by many factors, such as social, political, cultural and others.